(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1994)
Twenty-two conodont species are recognized in the Ockerkalk exposed in the Silius area (Gerrei, southeastern Sardinia). The fauna, which is the first reported from this peculiar facies, indicates a Ludlow and e.-m. Pridoli age for this limestone. Three conodont biozones (latialata, snajdri and crispa) are reported for the first time in Sardinia and, the Pelekysgnathus index horizon is newly recovered in Europe.